A review on durability properties of strain hardening fibre reinforced cementitious composites (SHFRCC) - Ahmed, Shaikh; Mihashi, H. (Pergamon, 2007)
This paper reviews and presents various durability properties of strain hardening fibre reinforced cementitious composites (SHFRCC). Published research results show that, due to its tight crack width properties compared to ordinary concrete and ordinary fibre reinforced concrete, SHFRCC significantly resists the migration of aggressive substances in to the concrete and improves the durabilityof reinforced concrete (RC). It is also reported that, due to the strain hardening and multiple cracking behaviours, SHFRCC meets the tight crack width limits for durability of RC structures proposed by different design codes. Based on the reviewed durability properties it is argued that SHFRCC materials can be used in selected locations of RC structural members to improve their overall durability performances.